2018
DOI: 10.18502/ijaai.v17i5.300
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Vascular Endothelial Growth Factor and Annexin A2 in Response to 4-(Methylnitrosamino)-1-(3-pyridyl)-1-Butanone -Induced Inflammation via Swimming Training

Abstract: The nitrosamine 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK; nicotine derived nitrosamine ketone) is one of the strongest carcinogens in tobacco which is involved in induction of lung cancer by changing the stimulation of vascular endothelial growth factor (VEGF) and annexin A2 expression. The aim of this study was to investigate the changes in resting levels of annexin A2 and VEGF in lung tissues of rats exposed NNK after 12 weeks of aerobic submaximal swimming training. For this purpose, 46 Wis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Collectively, studies in both humans and non-humans showed the association between symptoms of anxiety and higher cortisol and inflammatory markers [27][28][29]; further, and again in studies with humans and non-humans, swimming turned out to favorably impact symptoms of anxiety, as well as cortisol concentrations and inflammatory markers [23,24,26]. However, to our knowledge, no animal studies have investigated so far whether the favorable influence of swimming training (ST) could be observed also after the exposure to chronic mild stress and compared to a recovery period without further intervention.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Collectively, studies in both humans and non-humans showed the association between symptoms of anxiety and higher cortisol and inflammatory markers [27][28][29]; further, and again in studies with humans and non-humans, swimming turned out to favorably impact symptoms of anxiety, as well as cortisol concentrations and inflammatory markers [23,24,26]. However, to our knowledge, no animal studies have investigated so far whether the favorable influence of swimming training (ST) could be observed also after the exposure to chronic mild stress and compared to a recovery period without further intervention.…”
Section: Introductionmentioning
confidence: 88%
“…Likewise, Gomes da Silva [21] showed that that mild-to-moderate physical activity increased hippocampal anti-inflammatory cytokine levels in older rats. Moreover, swimming could reduce depressive-like behaviors in rats during pregnancy [22]; swimming increased the activity of the antioxidant enzyme superoxide dismutase (SOD) [23] and reduced oxidative damage by increasing proinflammatory cytokines [22] and SOD activity [24]. Further, and always among animal studies, swimming decreased IL-10 levels and oxidative stress and was associated with improved inflammation and inflammatory mediators (such as TNF-a, IL-6, and CRP) [25].…”
Section: Introductionmentioning
confidence: 98%